Analisis Faktor - Faktor yang Mempengaruhi Minat UMKM dalam Memilih Pembiayaan Bank Syariah - Winda Safitriyani; Achmad Kholiq; Dewi Fatmasari; Nur Haida (CIEBER: Contemporary Islamic Economic and Business Review, 2025)
This research aims to analyze the factors that influence the interest of MSMEs in Pilangsari Village in choosing sharia bank financing. This research uses a quantitative type of research. The sample in this study was Micro, Small and Medium Enterprises (MSMEs) in Pilangsari Village, totaling 80 respondents taken using proportional proportional sampling. Data collection techniques through distributing questionnaires and literature study. The data analysis used is descriptive analysis, statistical analysis in the form of validity and reliability tests, classical assumption tests, multiple linear regression tests, coefficient of determination tests (R^2) and hypothesis tests in the form of t tests (partial) and f tests (simultaneous) with using SPSS Statistics Version 22. The research results show that there is no influence between knowledge and financing procedures on the interest of Pilangsari Village Micro, Small and Medium Enterprises (MSMEs) in choosing sharia bank financing, and there is a positive and significant influence between promotion on the interest of Pilangsari Village MSMEs in choosing sharia bank financing and The calculated t value > t table is (2.862 > 2.227) with a significant value of 0.006 < 0.05. Simultaneously, Knowledge, Promotion and Financing Procedures together influence MSMEs' interest in choosing Islamic bank financing with a contribution of 15.9% while the remaining 84.1% is influenced by other variables not researched by the author.